HIGHER SECONDARY XI-STANDARD STUDENTS ATTITUDE TOWARDS SCHOOL AND PROBLEM OF SPEAKING IN ENGLISH - S. VIJAY KUMAR; DR. G. PANDIAN (International Journal of Innovations in Engineering Research and Technology, 2018)
This study is conducted to clear up the way that impact ofAttitude towards school and Problem of Speaking in English. This study involved XI standard students from 8 higher secondary schools in Namakkal district, Tamilnadu